All the rage eaudiobook - Frazier, T. M. (Tantor Media, 2016)
They call me Rage. My real name is like a shadow, always close behind but never quite able to catch up. I fly under the radar because no one ever suspects I'm capable of the kind of brutal violence I commit each and every day. You see, I'm a girl. I'm nineteen. And I'm a killer. This life is all I know. It's all I want to know. It keeps the things buried that I need kept buried. It allows me to live without thinking too much. Without dwelling on the past. Until him. It all changes when an ordinary boy becomes my next target. And my first love. I have to choose. The only life I've ever known has to die, or he does. Either way, I'll be the one pulling the trigger . . . Contains mature themes.